2020
DOI: 10.1111/ijcp.13608
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of parenteral versus parenteral and oral glucocorticoid therapy in Graves’ orbitopathy

Abstract: Graves orbitopathy (GO) is an autoimmune disorder of the retrobulbar tissue 1 probably initiated by autoreactive T lymphocytes which trigger a cascade of events including secretion of cytokines, 2 simulating proliferation of orbital fibroblastas, expansion of adipose tissue and secretion of glycosaminoglycans by the orbital fibroblasts. Therefore, immunosuppressants and anti-inflammatory agents are the treatment of choice for moderate-to-severe-and active GO. 3,4 Although different immunosuppressants including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Infusion should be slow (1–2 h) under close surveillance [80]. If facilities are not available, oral GCs represent an acceptable alternative [205]. Response to treatment usually occurs early but may become evident in the second half of the course [206, 207].…”
Section: Assessmentmentioning
confidence: 99%
“…Infusion should be slow (1–2 h) under close surveillance [80]. If facilities are not available, oral GCs represent an acceptable alternative [205]. Response to treatment usually occurs early but may become evident in the second half of the course [206, 207].…”
Section: Assessmentmentioning
confidence: 99%
“…Overall, 12 studies were included: 11 studies reported change from baseline in proptosis and 4 studies reported the proportion of patients with diplopia response. See eAppendix 2 and the eFigure in the Supplement for details …”
Section: Resultsmentioning
confidence: 99%
“…The MAIC analyses were conducted to compare IVMP and teprotumumab with each other and placebo for change from baseline in proptosis and diplopia response in 4 steps. First, data from the teprotumumab pooled trials were matched to the patient cohorts in the IVMP studies based on inclusion/exclusion criteria. Second, data were adjusted for outcome-specific prognostic factors (ie, patient characteristics that are associated with the outcomes) and treatment-effect modifiers (ie, patient characteristics that may affect the effectiveness of treatment on outcome) using inverse propensity score weighting.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 87 consecutive patients with clinically manifest TAO were recruited. All patients were regularly treated at the tertiary University Clinical Center of Serbia (Clinic for Endocrinology, Diabetes and Metabolic Diseases) according to the current guidelines and protocols [17] [18] [19] . Hormone analysis was carried out in all patients and the diagnosis was classified as Graves' disease (GD), Hashimoto's thyroiditis and euthyroid TAO.…”
Section: Methodsmentioning
confidence: 99%